Using Artificial Intelligence-based instructional strategies: An Approach of Responsible Special Education Teaching - Kashif Iqbal; Hania Amjad; Samina Ashraf; Irene Glendinning (Sustainable Business and Society in Emerging Economies)
Purpose: The purpose of this study was to examine the use of artificial intelligence-based instructional strategies that are the responsibility of special education teachers.